The impact of thin-capitalization rules on the location of multinational firms' foreign affiliates - Valeria Merlo; Nadine Riedel; Georg Wamser (Review of International Economics, 2019)
This paper examines how restrictions on the tax deductibility of interest cost affect location choices of multinational corporations (MNCs). Many countries have introduced so-called thin-capitalization rules (TCRs) to prevent MNCs from shifting their tax base to countries with lower tax rates. As of 2012, in our sample of 172 countries, 61 countries have implemented a TCR. Using information on nearly all new foreign investments of German MNCs, we provide a number of new and interesting insights in how TCRs affect the decision of where to locate foreign entities. In particular, stricter TCRs are found to negatively affect location choices of MNCs. Our results include estimates of own- and cross-elasticities of location choice and also novel results on the relative importance of tax base vs. tax rate effects. We finally provide estimates for different uncoordinated as well as coordinated policy scenarios.
Keywords: 330